General practitioners must acquire skills to communicate with child with Autism Spectrum Disorder to regain their values and role in the follow-up - phenomenological study - Bernard Clary; Eva Marengo-Sorli; Agnès Oude-Engberink; Elodie Million; Sylvain Pavageau; Michel Amouyal; Philippe Serayet; François Carbonnel; Gérard Bourrel; Béatrice Lognos (Taylor & Francis Group, 2021)
Objective To understand the perceptions and attitudes of general practitioners (GPs) regarding children with an Autism Spectrum Disorder (ASD). Design Phenomenological qualitative study. Setting Three focus groups, clinical settings. Subjects French GPs. Main outcome measures 22 GPs took part in the study divided among three focus groups. They were volunteers to participate. Data were transcribed verbatim and analysed using a grounded theory data analysis, completed with a semiopragmatic analysis. Results Representing autism as a strange disorder in the doctor-patient relationship, GPs perceive a loss of sensory contact with the child with ASD that prevents the usual professional relationship between doctor and patient. They disengage themselves from monitoring the subject, concentrating on supporting the family. According to them, their role was to refer the patient to a specialist in the case of clinical intuition, but they have several reasons to give themselves time, all the more so because once the diagnosis is made, they lose sight of the patient and their place in the care pathway. GPs expressed the need to acquire skills and strategies to communicate with the autistic child to recover their role and values. Conclusion GPs are disconcerted by the idea of communicating with children with ASD, as it takes them out of their usual professional benchmarks. They need communication tools that enable them to regain their role and relational value of the patient-centred approach. Beyond this, the question of the 'ethics of care' of the patient with a joint attention disorder is raised.KEY POINTS GPs are disconcerted with the idea of communicating with children with ASD. GPs need communication tools that enable them to regain their role and relational value of the patient-centred approach. The question of the 'ethics of care' of the patient with a joint attention disorder is raised.